2015
DOI: 10.1080/10408398.2015.1074533
|View full text |Cite
|
Sign up to set email alerts
|

Quality, functionality, and shelf life of fermented meat and meat products: A review

Abstract: Fermentation of meat is a traditional preservation method used widely for improving quality and shelf life of fermented meat products. Fermentation of meat causes a number of physical, biochemical, and microbial changes, which eventually impart functional properties, sensory characteristics, and nutritional aspects to these products and inhibit the growth of various pathogenic and spoilage microorganisms. These changes include acidification (carbohydrate catabolism), solubilization and gelation of myofibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 117 publications
2
48
0
2
Order By: Relevance
“…Similar LAB counts to those of this study have been reported in loins containing potentially probiotic strain L. acidophilus Bauer (Jaworska et al ., ). LAB counts for the control sample rose from 6.59 ± 0.27 on day 28 to 7.08 ± 0.26 on day 360 It is not surprising as lactobacilli are common in the natural microbiota of fermented meats (Kumar et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar LAB counts to those of this study have been reported in loins containing potentially probiotic strain L. acidophilus Bauer (Jaworska et al ., ). LAB counts for the control sample rose from 6.59 ± 0.27 on day 28 to 7.08 ± 0.26 on day 360 It is not surprising as lactobacilli are common in the natural microbiota of fermented meats (Kumar et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…). LAB counts for the control sample rose from 6.59 AE 0.27 on day 28 to 7.08 AE 0.26 on day 360 It is not surprising as lactobacilli are common in the natural microbiota of fermented meats (Kumar et al, 2017). Table 3 shows the proteolysis-related values of loins from day 90 to day 360 of storage, during which time TN content decreased while NPN content increased.…”
mentioning
confidence: 97%
“…This already fermented product contained the necessary microorganisms to start the fermentation of the new batch. This is known as back-slopping or back-inoculation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation is one of the oldest and most economical food‐processing and preservation methods contributing to nutritional value and resulting in pleasant flavors. During fermentation, desirable biochemical reactions, which are mainly conducted by lactic acid bacteria (LAB), produce significant modifications to the meat (Kumar et al., 2017). In this way, the production of Turkish‐fermented sausages (sucuk) is carried out in two main stages, namely, fermentation and drying.…”
Section: Introductionmentioning
confidence: 99%